Simuladores Dinamicos Computacionales, Principios de Operación - Vargas Tamayo, Luis Fernando; Contreras Bravo, Leonardo Emiro (Ingeniería, 2007)
Computerized 3D modeling systems have reached such degree of realism and definition that it is not only restricted to entertainment applications such as videogames and animation. Today, they are the development backbone of a constantly growing industry. Simulations called Tridimensional Virtual Reality are used in a variety of specific fields, such as architecture, flight simulations (aviation), surgery, etc. Special interest in the application of such software consists in the modeling of mechanic and dynamic systems, mechanisms and machinery. Aspects like tridimensional modeling,solidity control, assembly of parts and in some cases the interaction of moving objects are of great importance when they are analyzed in avirtually dynamic system.